![\: if \: \: 2^x = 3^y = 4^z , then \: \: \: prove \: \: \: that \: \: \: 1/x \: + \: \: 1/y \: \: - \: \: 1/z = 0 \: \: or \: \: z = xy/x+y \: if \: \: 2^x = 3^y = 4^z , then \: \: \: prove \: \: \: that \: \: \: 1/x \: + \: \: 1/y \: \: - \: \: 1/z = 0 \: \: or \: \: z = xy/x+y](https://tex.z-dn.net/?f=+%5C%3A+if++%5C%3A++%5C%3A+2%5Ex++%3D+3%5Ey+%3D+4%5Ez+%2C+then+%5C%3A++%5C%3A++%5C%3A++prove++%5C%3A++%5C%3A++%5C%3A+that++%5C%3A++%5C%3A++%5C%3A+1%2Fx++%5C%3A+%2B++%5C%3A++%5C%3A+1%2Fy++%5C%3A++%5C%3A+-+%5C%3A++%5C%3A+1%2Fz+%3D+0++%5C%3A++%5C%3A+or+%5C%3A++%5C%3A++z+%3D+xy%2Fx%2By)
Answers
Answered by
631
- 2^x = 3^y = 6^z = k
- 2^x = k [ 2 = k^1/x ]
- 3^y = k [ 3 = k^1/y ]
- 6^z = k [ 6 = k^1/z]
2 * 3 = 6 [ (k)^1/x * (k)^1/y = (k)^1/z
(k)^1/x + 1/y = (k)^1/z
ON EQUATING THE POWER FROM BOTH SIDE:
- 1/x + 1/y = 1/z
- 1/x + 1/y - 1/z = 0 [PROVED]
- 1/z = 1/x + 1/y
- 1/z = x + y / xy
- z = xy / x + y [PROVED]
ItsUDIT:
U can assume the number as any Alphabet
Similar questions